Mental Health DUKUNGAN KESEHATAN JIWA DAN PSIKOSOSIAL BAGI KELUARGA DI MASA PANDEMI - Agung Eko Hartanto; Yustina Purwaningsih; Gandes Widya Hendrawati (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
Indonesia and the world community are currently still busy with the outbreak of the corona virus pandemic (Covid-19). The increase in the number of cases and the impact of the pandemic felt by all levels of society including the family as the smallest unit. The presence of Covid-19 is a stressor for the community which can have an impact on mental and psychosocial health. Depression and anxiety about an illness cause strong emotional disturbances in both adults and children. Nurses' support for families in providing education and increasing mental health and psychosocial resilience is a priority during the current pandemic. PSKDJI data on mental health during the Covid-19 pandemic recorded 66% depression, 63% experiencing anxiety from 1,552 respondents. The purpose of this activity is to increase knowledge and ability to overcome psychosocial problems for families during a pandemic. The activities carried out are providing education accompanied by relaxation exercises. The participants' speed decreased from 9 (30%) to 2 (7%) after education and relaxation exercises.